La titrisation - Chambon, Benoît (Université Paris-Est, 2024)
Près de dix ans après la crise des subprimes les opérations de titrisation connaissent un nouvel essor. Ce dernier fait suite notamment à des travaux de la Commission européenne qui, dès 2015, a fait part de son intention de réviser le corpus applicable à ces transactions dans la cadre de son plan d'action pour la construction de l'Union des Marchés de Capitaux. C'est ainsi qu'en 2017 un règlement portant sur les opérations simples transparentes et standardisées a été publié au journal officiel de l'Union européenne. Ce texte a vocation à être complété par un autre règlement relatif à l'opposabilité des cessions de créances. Au niveau international les règles de rétention de fonds propres applicables visant les expositions de titrisations ont été amendées afin de mieux prendre en compte les risques y attachés. En France le régime applicable à la gestion d'actif et au financement par la dette a été remanié. On peut se demander comment ces évolutions normatives ont influencé la manière dont les risques systémiques et idiosyncratiques sont créés, transférés et couverts dans le cadre des opérations de titrisation. Almost ten years after the subprime crisis, securitization transactions are experiencing a new boom. The latter follows notably work of the European Commission which, as early as 2015, announced its intention to revise the legal framework applicable to these transactions as part of its action plan for the Capital Market Union. This led in 2017 to the publication in the Official Journal of the European Union of a regulation on simple, transparent and standardized transactions. This text is intended to be supplemented by another regulation on the enforceability of assignments of receivables. At the international level, the capital retention rules applicable to securitization exposures have been amended to take better account of the risks associated to said exposures. In France, the legal framework applicable to asset management and debt financing has been revised. One can wonder whether the normative developments have influenced the way systemic and idiosyncratic risks are created, transferred and hedged in securitization transactions.
Keywords: Idiosyncratic risks; Risque idiosyncratique; Risque systémique; Securitization; Systemic risks; Titrisation

Sermaye piyasası hukuku bakımından Mortgage - Aktaş, Mehmet Murat (Ankara Üniversitesi, 2024)
Türk mortgage sistemi veya mortgage menkul kıymetleştirmesi ve İpoteğe Dayalı Menkul Kıymetler-İDMK ihracı, sistemsel bütün olarak ilk kez uygulamada "Mortgage Kanunu" olarak da anılan 5582 sayılı "Konut Finansmanı Sistemine İlişkin Çeşitli Kanunlarda Değişiklik Yapılması Hakkındaki Kanun" (Konut Finansmanı Kanunu) ile 2007 yılında düzenlenmiştir. Meri'i düzenlemeler bakımından İDMK ihracı 6362 sayılı Sermaye Piyasası Kanunu (SerPK) madde 58 ve III-58.1 sayılı Varlığa ve İpoteğe Dayalı Menkul Kıymetler Tebliği (VİDMK Tebliği) ile düzenlenmiştir. Çalışmamızın amacı ve kapsamı, bünyesinde tek bir çalışmada ele alınması olanaksız sayıda hukuki düzenleme, kavram, kurum ve ilişki barındıran mortgage sistemini sermaye piyasası bakış açısıyla mevzuat tekrarlarından arındırılmış özlü tespit ve değerlendirmeleri esas alacak şekilde ele almaktır. Çalışmamızda mortgage sistemi kavramsal olarak gerçek anlamı ile ortaya konulacak ve ayrıca sistemin varlık nedeni ve özünü oluşturan sermaye piyasası unsuru olarak İDMK'ya ilişkin tespit, değerlendirme ve öneriler yer almaktadır. Mortgage ifadesi dar anlamda, Anglo-Sakson hukukunda kullanılan mortgage rehni ve mortgage teminatlı finansman alacaklarını ifade etmektedir. Mortgage terimi, sermaye ve finans piyasaları bakımından ise mortgage teminatlı alacakların İpoteğe Dayalı Menkul Kıymetler (İDMK/mortgage-backed securities-MBS) ihraç edilerek menkul kıymetleştirildiği (securitization) sistemi anlatmaktadır. Mortgage sistemi veya menkul kıymetleştirmesi ve İDMK ihracı ilk olarak Amerika Birleşik Devletleri (ABD) hukukunda uygulanmıştır. Mortgage sisteminin varlık nedeni, sermaye piyasalarından İDMK ihracı yoluyla en az maliyetle ve güvenilir bir şekilde finansman sağlanmasıdır. İDMK ihracı, mortgage (ipotek) teminatlı finansman alacaklarının, mortgage sistemi içerisinde gerçek satışa (true sale) dayalı olarak bilânço dışına çıkarılması ve menkul kıymetleştirilmesi ile gerçekleştirilmektedir. Bu nedenle İDMK, gerçek satışa dayalı bilânço dışı olarak gerçekleştirilen gerçek (geleneksel) menkul kıymetleştirme ürünü bir menkul kıymet niteliğindedir. Toplam beş bölümden oluşan Tez çalışmamızın ilk bölümünde, mortgage sistemi kavramı teknik anlamıyla değerlendirilecek, sistemin tarihi gelişim süreci ve ilişkili düzenlemeler ve niteliği olarak menkul kıymetleştirme ele alınacaktır. Çalışmamızın ikinci bölümünde, mortgage sisteminin işleyişi, sistemde kullanılan varlıklar ve safhaları, sistemin özgün terminolojisi berberinde değerlendirilecektir. Çalışmamızın üçüncü bölümünde ise mortgage sisteminde yer alan kuruluşlar gene sistemin kendine özgü kavram ve gereklilikleri dahilinde değerlendirilecektir. Çalışmamızın dördüncü bölümünde sistemin hedefi ve varlık sebebi olan İDMK tanımı türleri ve benzeri menkul kıymetler beraberinde ele alınacaktır. Çalışmamızın beşinci ve son bölümünde ise İDMK ihracı ile sağlanan sebepler ve ihracını güçleştiren sebeplere dair tespit ve önerilerimiz topluca yer alacaktır. Tezimizin sonuç kısmında ise gerçek anlamıyla uygulanması halinde ülkemizin hızlı ve sürdürülebilir bir biçimde kalkınmasını sağlayabilecek niteliği haiz bir sistem olan mortgage sistemi ve onun ürünü menkul kıymet olan İDMK'nın ihracı bakımından tespit ve çıkarımlarımız yer alacaktır. Tezimiz genel olarak Türkiye'nin finansal kurumlara, İDMK'yı, iç pazardaki ekonomik kalkınmayı hızlandırmak için sermaye piyasalarından fon sağlamak için kullanma önerisi de getirmektedir. Bu tez ile Türkiye'de finans kurumlarının MBS ihraçları için alternatif bir finansman kaynağı olarak dikkat çekilmesi de amaçlanmaktadır. Burada kamusal bir gelişme olarak ifade edilecek olursak, "Yeni Ekonomi Program", finansal derinliğin ve istikrarın sağlanması için Türkiye'deki menkul kıymetleştirmelerin (İDMK ihraçları dahildir) desteklenmesi tedbirini de içermektedir. The Turkish mortgage system, mortgage securitization, and the issuance of Mortgage-Backed Securities (MBS), collectively referred to as the "Mortgage Law," were initially regulated in 2007 by Law No. 5582, also known as the "Law on Various Amendments Regarding the Housing Finance System" (Housing Finance Law), commonly referred to as the "Mortgage Law" in practical application. In terms of secondary regulations, the issuance of MBS is governed by Article 58 of the Capital Markets Law No. 6362 (CML) and the Communiqué on Asset-Backed Securities and Mortgage-Backed Securities (ABS-MBS Communiqué). The aim and scope of this study involve a comprehensive examination of the mortgage system, which encompasses numerous legal regulations, concepts, institutions, and relationships. The focus is on providing concise assessments and evaluations, free from legal redundancies, based on the perspective of capital markets. The study conceptually presents the mortgage system in its true sense, addressing the essence and purpose of the system, particularly focusing on Mortgage-Backed Securities (MBS) as a capital market element, along with relevant findings, evaluations, and recommendations. In a narrow sense, the term "mortgage" refers to the mortgage lien and financing receivables secured by mortgages in Anglo-Saxon law. In the context of capital and financial markets, the mortgage system refers to the securitization of mortgage-backed receivables by issuing Mortgage-Backed Securities (MBS). The mortgage system, its securitization, and MBS issuance were initially implemented in the United States (US) legal framework. The raison d'être of the mortgage system lies in obtaining financing from capital markets through the issuance of MBS at minimal cost and in a reliable manner. MBS issuance involves transferring mortgage-backed financing receivables out of the balance sheet through a true sale mechanism within the mortgage system, facilitating their securitization. Therefore, MBS represents a security of a true sale-based, off-balance-sheet, and traditional nature. The thesis comprises five sections. The first section evaluates the concept of the mortgage system in technical terms, discussing its historical development, related regulations, and its nature as securitization. The second section delves into the operation of the mortgage system, the assets used, stages involved, and the system's unique terminology. The third section examines the institutions within the mortgage system, considering their specific concepts and requirements. The fourth section covers the objective of the system and the definition of MBS, its types, and similar securities. The fifth and final section consolidates our findings and recommendations regarding the reasons for MBS issuance and the challenges hindering it. In the conclusion, we highlight the potential of the mortgage system and its product, MBS, as a system capable of fostering rapid and sustainable development in Turkey when implemented in its true sense. The thesis suggests that financial institutions in Turkey consider MBS issuances as an alternative source of funding, aiming to accelerate economic development in the domestic market. Additionally, the study aligns with the "New Economic Program," which includes measures to support securitizations in Turkey, including MBS issuances, to ensure financial depth and stability.
Tez N°865004
Keywords: Capital market; Hypothèque; Menkul kıymetleştirme; Mortgage; Mortgage Backed Securities; Securtization; Sermaye Piyasası Hukuku; Sûretés; İpoteğe Dayalı Menkul Kıymetler

Reserva e alienação em garantia no direito da OHADA - Sampa, Samora Ilídio Delgado (Universidade de Lisboa, 2023)
O presente estudo aborda o tema da alienação fiduciária em garantia no âmbito da OHADA e do Direito positivo da Guiné-Bissau. A alienação fiduciária tem vindo a assumir uma importância decisiva no comércio jurídico internacional e no mercado de alta finança. A alienação fiduciária em garantia é um instituto com raízes no Direito Romano “fiducia cum creditore”. A evolução histórica da fidúcia revela que o instituto tem tendência para reaparecer nos momentos em que o Direito positivo se mostra inadequado para acompanhar novas necessidades sociais e económicas, nomeadamente a procura de garantias com a facilidade de constituição e execução. Actualmente, os negócios fiduciários têm raízes sólidas nos Direitos Civis de base romanística e continuam a influenciar o Direito Europeu e todos os Direitos que nele se inspiram, nomeadamente a OHADA, que instituiu, em 2010, a figura da alienação em garantia, em especial, cessão de crédito em garantia e alienação fiduciária de dinheiro em garantia. Um dos desafios das garantias fiduciárias instituídas pela OHADA é a falta da sua articulação saudável com os institutos fundamentais do Direito Civil, porque o novel Acto Uniforme não contém um regime fiduciário em geral e existem outros aspectos que suscitam dúvidas e carecem de aperfeiçoamentos. Todavia, o regime da alienação em garantia instituído pela OHADA revela, de um modo geral, ser favorável ao credor, facto manifesto ao nível dos mecanismos da execução da garantia, pois permite ao credor recorrer aos meios tradicionais da execução da garantia - via judicial – assim como a execução por via convencional ou através do pacto marciano - obrigando sempre ao credor à restituir a diferença na execução da garantia. Cette étude aborde le thème de l’aliénation fiduciaire en garantie dans le cadre de l'OHADA et du droit positif dans la Guinée - Bissau. L’aliénation fiduciaire a joué un rôle décisif dans le commerce juridique international et sur le marché de la haute finance. L’aliénation fiduciaire en garantie c`est un institut aux racines du Droit Romain «fiducia cum creditore». L’évolution historique de la fiducie montre que l’institut a tendance à réapparaître à des moments où le Droit positif est insuffisant pour faire face aux nouveaux besoins sociaux et économiques, à savoir la recherche de garanties avec la facilité de constitution et de réalisation. Actuellement, les contractes fiduciaires ont des racines solides dans les droits civils fondés sur le Droit Romain et continuent d’influencer le Droit européen et tous les droits sur lesquels elle s’appuie, à savoir l’OHADA, qui a établi en 2010 la fiducie – sûreté, en particulier la cession de créances en garanties, la réserve de propriété et la cession fiduciaire de la somme monétaire en garanties. Un des défis des garanties fiduciaires instituées par l’OHADA est l’absence de son articulation saine avec les instituts fondamentaux de Droit Civil, car le nouvel acte uniforme ne contient pas de régime général de la fiducie et il y a d’autres aspects qui soulèvent des doutes et manque des enquêtes et de l’approfondissement. Cependant, le régime de la fiducie – sûretés établi par OHADA est d’une façon générale, favorable au créancier, ce qui est confirmé au niveau des mécanismes d’exécution de la garantie, car ils permettent au créancier d’utiliser les moyens traditionnels d’exécution de la garantie - judiciairement - ainsi que l’exécution par convention ou par le biais du pacte martien - obligeant toujours le créancier à rétablir la différence dans l’exécution de la garantie.
Keywords: Alienação; Aliénation; Fiduciaire; Fiduciária; Garantia das obrigações; Garantie d’obligations; OHADA

The Law Applicable to Security Interests in Intermediated Securities under OHADA Law - Monsenepwo Mwakwaye, Justin (Universität Würzburg, 2022)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwoaims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Competencia; Competition law

Le report de la sûreté sur l’obligation de restitution : analyse de l’Article 1352-9 du Code civil - Dardenne, Aurélie (Université Paris 2, 2022)
En 1982, la Cour de cassation opère un revirement de jurisprudence en considérant que le cautionnement initial est amené à garantir les restitutions découlant de l’anéantissement du contrat. Cette solution, des plus étonnantes, a dans un premier temps été considérée comme un épiphénomène par la doctrine. Toutefois, elle s’est maintenue et même étendue à d’autres sûretés comme l’hypothèque ou le privilège du prêteur de denier. Par l’ordonnance du 10 février 2016, une étape supplémentaire est franchie : la règle se trouve consacrée à l’article 1352-9 du Code civil. L’analyse théorique de la règle nous apprend que celle-ci rentre en contradiction avec les principaux principes guidant notre droit des contrats et notre droit des sûretés. En effet, cette disposition opère une survie fictive de la sûreté, réalisée au mépris du principe de l’accessoire et un transfert fictif de celle-ci d’une obligation à l’autre, qui méconnaît le principe de rétroactivité de l’anéantissement du contrat. L’explication de la généralisation doit donc se trouver ailleurs, dans la politique juridique : le report de la sûreté sur l’obligation de restitution permet d’aborder une sécurité au créancier des restitutions sans aggraver le sort du garant. Cependant, l’analyse pratique de la règle contredit cette conclusion. Le champ d’application de l’article 1352-9 du Code civil est d’abord mal défini. Dans un certain nombre de cas, la règle ne peut s’appliquer et dans les hypothèses où elle pourrait fonctionner, elle s’avère bien souvent inefficace voire même inutile. = In 1982, the Court of cassation decided to extend the scope of payment guarantee to the restitutions, which are the consequences of a void contract or of the termination of contract. This solution was quite unexpected as it conflicted with two important rules of our legal system. Firstly, it goes again the retroactivity of contract cancellation. Secondly, it is opposed to the « accessory rule », which is a frame of our proprietary security interest law. In spite of these criticisms, this rule was not only introduced in the French civil Code in 2016, but also generalized at all kind of security rights. What could explain this generalization? We show that this rule aims for the security of the creditor in the restituary phase. In accordance with this statement, we can link this solution with the analysis of law’s current trend. In other words, the article 1352-9 of French civil Code is a way of restoring the efficiency of security rights. However, in practical application, this goal is not achieved. The article 1352-9 of French civil Code is inaccurate as the application field isn’t well defined. In many cases, the rule can’t be applied and in other, it is simply inefficient or useless.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2022ASSA0044
Keywords: Cautionnement; Contract Law; Contrat; Contrats; Guarantee; Hypothèque; Invalidity of contract; Invalidity; retroactivity; Law of restitution; Morgage; Nullité (droit); Nullité du contrat; Payment guarantee; Privilèges mobiliers; Quasi-contract; Quasi-contrat; Restitution; Restitution (droit); Résolution du contrat; Rétroactivité de la nullité contractuelle; Security right; Sûretés; Termination of contract

La caution profane - Ouattara, Aboudou (Université de Montpellier, 2022)
Le cautionnement contemporain est marqué par la diversité des personnes impliquées dans l’opération juridique, dont la dangerosité invite à un traitement et une application différenciés de règles qui le régissent. À cet égard, la jurisprudence a consacré la notion de caution profane en procédant par un, qui bénéficie de son indulgence. Considérée comme la partie faible et vulnérable du contrat de cautionnement, elle désigne toute caution personne physique qui n’est pas mesure de comprendre la nature de son engagement et d’en apprécier la portée, au regard de ses connaissances et de sa compétence. À défaut d’une réforme globale, les réformes législatives successives du droit du cautionnement ont étendu les règles nouvelles à toutes les personnes physiques, quelles qu’elles soient, affaiblissant ainsi, le cautionnement dont la fonction est d’assurer le crédit. Le législateur s’est donné pour objectif dans la loi n° 2019-486 du 22 mai, dite loi Pacte, de réformer le droit des sûretés afin de renforcer son efficacité et, à propos du cautionnement, conforter la sécurité des créanciers et assurer la protection de la caution personne physique. La qualité de caution profane, bien qu’indispensable dans l’application prétorienne des règles du droit du cautionnement, n’a malheureusement pas été consacré par l’ordonnance n° 2021-1192 du 15 septembre 2021 portant réforme du droit des sûretés, qui rentrera en vigueur le 1er janvier 2022.Cette étude entend contribuer à la reconnaissance légale de la qualité de caution profane afin de réduire l’application casuistique qui en est faite par la jurisprudence.
Keywords: Avertie; Cautionnement; Cautions (personnes); Déséquilibre; Incompétence; Inégalité; Profane; Sûretés (droit)

La réception de l'agent des sûretés par le droit français - Larrain, Bernardo Garcia (Université Paris 1, 2022)
Le droit français du financement est en constante mutation afin de permettre aux praticiens de réaliser des opérations de plus en plus complexes au regard de leur montant et des éléments d’extranéité qu’elles comportent. La réception de la figure de l’agent des sûretés par le droit français constitue un exemple de cette évolution. L’agent des sûretés est la personne nommée par un groupe de banques dont la mission consiste à prendre, inscrire, gérer et réaliser les sûretés destinées à garantir une opération de crédit syndiqué. Très utilisée dans la pratique internationale et en droit anglais, où elle prend la forme du trust, la figure de l’agent des sûretés a longtemps été absente du droit français. Cette situation a constitué un élément défavorable à la France dans la compétition à laquelle se livrent les systèmes juridiques sur le marché des financements internationaux. La réception de l’agent des sûretés par le droit français a été longue et marquée par différentes étapes. Dans un premier temps, confrontés à l’absence de la figure du trust en droit français, les praticiens français ont essayé de franchir cet obstacle en ayant recours au contrat de mandat du Code civil, ou à d’autres figures prévues par le droit français. Parallèlement, des dispositifs issus de droits étrangers, tels que le security trustee et la « dette parallèle », ont été employés au risque de ne pas être pleinement efficaces en France. Dans un second temps, le législateur a essayé de combler ce vide en instituant pour la première fois l’agent des sûretés en droit français à travers son introduction dans le Code civil en 2007. Cette innovation se révélera cependant peu adaptée et ne sera donc pratiquement pas utilisée. Ce n’est qu’en 2017 que la France s’est dotée d’un régime d’agent des sûretés digne de ce nom et qui semble être adapté à la pratique des crédits syndiqués.
Keywords: Agent de crédit; Agent des sûretés; Arrangeur; Banques (droit); Crédit (gestion); Crédit syndiqué; Dette parallèle; Fiducie; Syndication bancaire; Syndicats financiers; Sûretés

Letters of credit and demand guarantees : a legal study on the impact of targeted financial sanctions from a South African perspective - Lupton, Cayle Selwyn (University of Johannesburg, 2022)
The purpose of this study is to provide a legal analysis of the impact of targeted financial sanctions on letters of credit and demand guarantees. The letter of credit is an important method of payment used in international trade. The demand guarantee plays a significant role as an instrument of security in commercial transactions. In their simplest form both instruments constitute an undertaking by a bank to pay a beneficiary against delivery of certain stipulated documents. Letters of credit and demand guarantees are known to be reliable and provide a considerable measure of certainty and predictability to the underlying transaction. Consequently, they have been described as the “lifeblood of international commerce”. Targeted financial sanctions entail assets freezing and prohibitions to prevent funds or other assets from being made available, directly or indirectly, for the benefit of designated individuals and entities. Endorsed by the United Nations and implemented by the vast majority of jurisdictions around the world, targeted financial sanctions are increasingly being used to combat financial crime, including money laundering, terrorism financing and weapon proliferation financing. Banks play a critical role in financial crime prevention and detection. Hence they have been identified as institutions that must comply with targeted financial sanctions. The relationship between targeted financial sanctions and letters of credit and demand guarantees has generally not been well documented. It is hoped, therefore, that this study will make a meaningful contribution to the jurisprudence on letters of credit and demand guarantees. In investigating the impact of targeted financial sanctions, the study can be categorised into three parts. Part one investigates a bank’s compliance with domestic targeted financial sanctions. The chief findings of the study in this regard are that banks are under a legal obligation to comply with sanctions and, as a result, a bank that refuses to perform its contractual obligations under a letter of credit or demand guarantee may have a defence in law. In South African law the bank can raise the so-called defence of legal impossibility of performance to resist a claim for, or potential litigation in respect of, payment. Part two investigates a bank’s compliance with foreign targeted financial sanctions. Because compliance in this regard has no (legal) basis, the bank may conceivably be sued by the beneficiary for payment on the basis of breach of contract. Part three investigates problematic documentary practices that banks have adopted or conceivably may adopt to manage their sanctions risk exposure. In this regard, attention is given to so-called sanctions clauses and other non-documentary conditions. The issue of unjustified amendments by the beneficiary for the purposes of sanctions evasion is also considered in part three. The general conclusion arrived at is that by interfering with payment, targeted financial sanctions render letters of credit and demand guarantees unreliable, thereby having the effect of reducing their value to international trade and commerce. The author proposes certain recommendations and initiatives aimed at mitigating the impact of targeted financial sanctions on credits and guarantees. Key terms: letters of credit; demand guarantees; financial crime; sanctions evasion; targeted financial sanctions; compliance; banks; due diligence; payment; reimbursement; credits; guarantees.
Keywords: Banks; Compliance; Credits; Demand guarantees; Due diligence; Financial crime; Guarantees; Letters of credit; Payment; Reimbursement; Sanctions evasion; Targeted financial sanctions

L'incidence de l'arbitrage et les situations triangulaires : Étude à la lumière de l'évolution du sort de la caution solidaire - El Hajj, Joyce (Université de Montpellier, 2021)
La Cour de cassation a mis fin aux controverses jurisprudentielles et doctrinales sur la qualité de la caution solidaire quant à la clause compromissoire, et cela en refusant l’application de la théorie de la représentation mutuelle des coobligés et en la qualifiant de « tierce personne », ouvrant par ce fait la porte à la tierce opposition. La transposition de la solution avancée par la Haute Cour, a été parfaitement appliquée à l’assureur non-signataire de la clause compromissoire insérée dans un contrat liant son assuré à une autre personne, même en présence de la clause de direction de procès dans le contrat d’assurance. Enfin, la possibilité de l’application de cette solution a été étudiée au cas par cas sur l’effet de la clause compromissoire statutaire à l’égard d’un futur ou ex- associé. The Court of Cassation put an end to the jurisprudential and doctrinal controversies on the quality of the joint and several sureties regarding the compromise clause, and this by refusing the application of the theory of mutual representation of the co-owners and by characterizing it as “third party”, thereby opening the door to the third-party opposition. The transposition of the solution proposed by the High Court was perfectly applied to the insurer who did not sign the arbitration clause inserted in a contract binding his insured person to another person, even in the presence of the trial management clause in the insurance contract. Finally, the possibility of applying this solution has been studied on a case-by-case basis on the effect of the statutory arbitration clause on a future or ex-partner.
Keywords: Arbitrage; Arbitragem; Arbitration; Assureur non-Signataire; Caution solidaire; Cautionnement; Clause compromissoire; Codébiteurs; Corporate law; Droit des sociétés; Joint and several sureties; Non-Signatory insurer; Third party; Tierce opposition; Tiers (droit)

Le sort des créanciers d'un débiteur en difficultés en droit OHADA à la lumière du droit français : l'égalité en question - Owona-Atangana, Dominique (Université Paris 1, 2021)
La thèse veut déterminer le périmètre de l'égalité pour comparer les législations OHADA et française. Le choix du créancier chirographaire comme modèle s'est imposé parce que le droit de gage général est sa seule garantie d'exécution des obligations monétaires du débiteur et le plus petit dénominateur commun entre tous les créanciers. Assis sur les biens du débiteur, il condamne à l'égalité du paiement en cas de concours entre créanciers chirographaires et la soumission à un principe d'égalité des créanciers chirographaires. Mais ce périmètre n'a pas pu être établi. Peu de créanciers sont « chirographaires » et peu de biens du débiteur sont soumis à la saisie d'où procède le concours duquel surgit l'égalité du paiement; même par application d'un principe d'égalité lequel oblige seulement créanciers et débiteur à mutualiser le risque de l'entreprise en observant un comportement loyal. Ainsi, contrairement au créancier chirographaire « modèle » ou « déloyal », le créancier chirographaire « stratège » peu prendre place à la procédure collective dans la catégorie assignée par contrat de sûreté loyal pour y subir l'égalité des chances. Autrement dit, la prolifération des sûretés conventionnelles apporte plus à l'égalité des créanciers que l'affectation du gage commun à leur satisfaction puisqu'en dehors des créanciers munis d'une sûreté inefficace, insuffisante ou inopposable, on peine à identifier un créancier chirographaire la procédure collective. Désormais, il faut élever le débat de l'égalité des créanciers au niveau de ceux échappant au lot commun. De ce point de vue la législation française par la variété des sûretés proposées protège plus que la législation OHADA. The thesis aims to determine the scope of equality in order to compare OHADA and French legislation. The choice of the unsecured creditor as a model was imposed because the general lien is its only guarantee of performance of the debtor's monetary obligations and the lowest common denominator among all creditors. Sitting on the debtor's property, he condemns equal payment in the event of a competition between unsecured creditors and submission to a principle of unsecured creditors. But this perimeter could not be established. Few creditors are ''unsecured'' And few of the debtor’s assets are subject to seizure from which proceeds the competition which results in equality of payment ; even by applying a principle of equalitu, which only obliges creditors and debtors to mutualize the risk of the compagny by observing fair behavior. Thus, unlike the ''model'' or ''disloyal'' unsecured creditot, the ''strategic'' unsecured creditot can take place in bankrupty proceedings in the category assigned by a fair security contract to undergo equal opportunities. In other words, the proliferation of conventional sureties brings more to the equality or creditors than the allocation of the common pledge to their satisfaction since, apart from creditors provided with ineffective, insufficient or unenforceable security, it is difficult to identify an unsecured creditor, collective proceedings. Now, the debate on the equality of creditors must be raised to the level of those outside the common lot. From this point of view, French legislation, through the variety of securities offered, protects more than OHADA legislation.
Keywords: Créancier chirographaire; Droit comparé; Droit de gage général; Droit des affaires; Egalité du paiement; Entreprises en difficultés; Equal payment; Equality in order; France; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Principe d'égalité; Procédure de liquidation; Sûretés conventionnelles; Unsecured creditor

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

La summa divisio des sûretés pour soi et des sûretés pour autrui - Crastre, Julie (Université Paris 1, 2020)
De lege lata, la summa divisio des sûretés personnelles et des sûretés réelles ne permet plus d'apporter une lecture claire du droit applicable. C'est ainsi qu'une nouvelle distinction apparaît au grand jour, opposant les sûretés pour autrui aux sûretés pour soi. Le fait de s'engager à garantir la créance d'autrui implique une absence de contrepartie directe à l'engagement tandis que lorsque le constituant s'engage pour lui-même il bénéficiera, par hypothèse, directement du succès de l'opération garantie. La notion de contrepartie renvoie directement à la cause des contrats. La confrontation entre les sûretés et la cause aboutit à l'interpréter par le prisme de la notion d'intérêt. Le garant pour autrui poursuivra la satisfaction d'un intérêt altruiste ou patrimonial. Or à l'inverse du constituant d'une sûreté pour soi, l'intérêt patrimonial ne sera jamais direct en raison de l'intermédiation d'un patrimoine tiers faisant obstacle à la réception immédiate des fruits de l'opération garantie. La cause met en lumière la gravité des sûretés pour autrui et représente ainsi le critère de séparation entre les deux catégories de sûretés. Une fois scellée, nous pouvons constater que la distinction influence le régime juridique de la sûreté tout au long de sa vie, y compris en cas d'ouverture d'une procédure collective. Deux lignes directrices se révèlent : la préservation du garant pour autrui face au risque de surendettement et la protection de l'efficacité juridique de la sûreté pour soi. Le rayonnement de la distinction des sûretés pour soi et des sûretés pour autrui autorise à la considérer comme étant la summa divisio fondamentale des sûretés. De lege lata, the summa divisio between persona! guarantees and lien sureties is not as relevant as it used to be. A new distinction between sureties for oneself and sureties for others appears to be more efficient. Guaranteeing someone else's debt implies a lack of any direct benefit in exchange for the contractual bond, whereas guaranteeing one's own debt is an operation that serves the same interest as the one present in the guaranteed transaction. The idea of benefit stems from the "cause of the contract", which has to be interpreted through the notion of interest. Someone who guarantees someone else's debt is driven by a selfless or a financial interest. But this financial interest can never be a direct one. Analysing sureties through this new perspective helps understanding the dangers of a surety for oneself. Therefore, the cause of the contract is a tool for distinguishing two types of sureties. This distinction - between sureties for oneself and sureties for others - leads to coherent sets of rules that can be applied to each of the two types of sureties. Each of these sets of rules is guided by a different philosophy: protecting the guarantor, bound for the benefit of someone else on the one hand, and ensuring the efficiency of the surety for oneself on the other hand. The outreach of this distinction between sureties points to a new way to look at the French sureties by adopting a new summa divisio between sureties for oneself and sureties for others.
Keywords: Classification des contrats; Contract law; Corporate law; Droit d'obligations; Droit de sûretés; Droit des procédures collectives; Droit des sociétés; Obligations (droit); Procedural law; Security law; Sûretés

Essai d'une théorie générale des sûretés réelles : plaidoyer pour la réhabilitation du droit de préférence - Lledo, Charlie (Université Paris 2, 2020)
Réformé par petites touches à une dizaine de reprises depuis le début du siècle, le droit des sûretés peine à trouver sa cohérence. Les sûretés réelles sont les victimes principales de cette instabilité. En effet, tant le développement des garanties exclusives, qu’elles reposent sur la propriété ou la rétention, que celui des sûretés pour autrui, ont considérablement brouillé le concept même de sûreté réelle. Par ailleurs, les contraintes imposées aux créanciers par le droit des procédures collectives et l’inflation constante du nombre de privilèges ont poussé les créanciers à rechercher systématiquement leur salut dans l’exclusivité, dont le régime est bien plus protecteur que celui des sûretés « traditionnelles », octroyant un simple droit de préférence. Par contrecoup, les objectifs du droit des procédures collectives sont plus difficiles à atteindre et de plus en plus de créanciers voient leurs droits partir en fumée. La présente thèse a pour objectif de démontrer que c’est de la restauration de l’efficacité du droit de préférence que peut revenir la cohérence du droit des sûretés réelles, et qu’elle seule est à même de permettre d’atteindre un modus vivendi acceptable entre les intérêts des constituants, des créanciers, des tiers et des entreprises en difficulté. = As it has been abundantly amended since the beginning of the century, the law of guarantees has begun to lose its coherence. Guarantees on goods suffer the most from this instability. Indeed, as exclusive guarantees and guarantees for the debt of others extended their empire, the concept of guarantee on goods has become muddled. Simultaneously, bankruptcy laws and the constant rise in the numbers of privileges have provided a powerful incentive for creditors to choose exclusive guarantees over preferential ones. As a result, some of them can be paid in full, whereas most of them receive nothing, and the goals pursued by bankruptcy laws tend to be a lot harder to attain. This thesis aspires to demonstrate that the rehabilitation of preferential rights is necessary to restore the coherence of securities on goods laws. It is, in fact, the only way to come to an agreement between the interests of debtors, creditors, third parties and bankrupt companies.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2020PA020013
Keywords: Bankruptcy Law; Cautionnement réel; Collateral; Droit de rétention; Entreprises en difficulté; Fiducie; France; France; 21st century; France; XXIe siècle; Garanties; Guarantees; Leasing; Privileges; Privilèges; Privilèges (droit) - France; Privilèges (droit) – France; Procédures collectives; Reservation of Title; Réserve de propriété; Security interest; Surety; Sûretés; Sûretés personnelles; Sûretés réelles

La notion de gage général - Risser, Julien (Université de Lorraine, 2020)
Quiconque s’est obligé personnellement, est tenu de remplir son engagement sur tous ses biens mobiliers et immobiliers, présents et à venir. C’est par cette formule lumineuse que l’article 2284 du Code civil (ancien article 2092 du Code Napoléon) introduit en droit français ce qu’il est convenu d’appeler le gage général. Incontournable en droit privé, invoquée par la doctrine, la jurisprudence et même la loi, cette notion n’a, paradoxalement, fait l’objet d’aucune étude approfondie. Le gage général ne manque pourtant pas d’actualité, l’introduction du patrimoine d’affectation à travers la fiducie et l’EIRL ne constituant que l’arbre qui cache la forêt. Successions, régimes matrimoniaux, procédures civiles d’exécution, cautionnement, insolvabilité, autant de matières dont les évolutions affectent le mécanisme de responsabilité patrimoniale du débiteur. D’aucuns avancent que ces évolutions signeraient le déclin, voire la disparition de la notion de gage général. L’affirmation se justifie-t-elle ? Il convenait, pour le vérifier, de déterminer les contours et le contenu de la notion avant de mesurer les modifications engendrées par le droit contemporain. À partir d’une analyse approfondie des réflexions doctrinales, il est proposé une identification précise de la notion de gage général, mettant en exergue son rôle central dans l’obligation. Une fois la notion identifiée, l’étude apporte un éclairage sur les diverses évolutions du droit privé qui ont mis à l’épreuve le gage général, ainsi que sur les évolutions du droit public qui ont fait émerger la notion dans un champ du droit qui lui était jusqu’ici inconnu.
Keywords: Action oblique; Action paulienne; Dessaisissement; Exécution forcée; Gage (droit); Immunité d’exécution; Indisponibilité; Insaisissabilité; Insolvabilité; Obligation; Obligations (droit); Patrimoine; Patrimoine d’affectation; Procédures civiles d’exécution; Saisie; Sûretés (droit)

La réception des sûretés sur biens incorporels dans l'ordre international - Mennucci-Maillard, Alexandre (Université Paris 2, 2020)
Dans le monde actuel, l’active circulation des hommes et des marchandises conduit à une importante utilisation des sûretés réelles – notamment sur biens incorporels (créances, droits de propriété intellectuelle, titres financiers, etc.) – en garantie d’opérations de crédit international. Dans l’ordre international, il n’existe pas (encore ?) de sûreté sur bien incorporel uniforme, doté d’un régime commun pour tous les pays ; les garanties réelles restent adossées à des ordres juridiques de référence. L’enjeu consiste donc à déterminer de quelle manière il conviendrait de donner effet, dans l’ordre juridique français, aux sûretés sur biens incorporels constituées à l’étranger. Si la méthode de la reconnaissance semble disqualifiée en raison d’obstacles techniques, politiques et jurisprudentiels trop importants et des difficultés de détermination d’un ordre juridique de référence unique, celle de l’adaptation de la sûreté étrangère par assimilation à une sûreté locale de rattachement paraît la plus pertinente, au regard notamment de la protection des intérêts de chacun – créanciers, étrangers et nationaux, et débiteurs. = In today's world, the active movement of people and goods leads to an equally important use of security interests – particularly in intangible assets (receivables, intellectual property rights, financial securities, etc.) – as collateral for international credit transactions. There is (as yet?) no uniform security interest on intangible collateral with a common regime for all countries. In the International Law, security interests remain attached to a national legal system. The issue is therefore to determine how it would be appropriate to give effect, in France, to those security interests in intangible assets. While the method of recognition seems to be disqualified because of excessive technical, political and judicial obstacles and the lack of unicity of the applicable laws, the method of adapting the foreign security right by assimilation to a local security right seems the most relevant, particularly with regard to the protection of the interests of each party – creditors, foreign or domestic, and debtors.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2020PA020025
Keywords: Adaptation; Bankruptcy; Bien incorporel; Biens incorporels; Conflict of laws; Conflits de lois; Droit international privé; Insolvency; Intangible collateral; Lien; Lois de police; Mandatory rules; Nantissement; Numerus clausus; Opposabilité; Procédures collectives; Recognition; Reconnaissance; Security interest; Seizure; Sûretés; Sûretés réelles

La proportionnalité des sûretés - Blondel, Marie (Université Paris-Est, 2020)
La thèse propose de montrer que la proportionnalité des sûretés remplit deux fonctions bien distinctes.En premier lieu, la proportionnalité permet de lutter contre l’insolvabilité des garants, ces personnes qui répondent du crédit consenti sans en bénéficier. Elle s’entend alors de l’adéquation entre le montant de la sûreté pour autrui et les facultés de paiement du garant. La règle, d’ores et déjà consacrée en matière de cautionnement, mérite d’être à la fois restreinte aux garants de bonne foi, mais aussi étendue à tous les garants personnes physiques, qu’ils aient souscrit une garantie autonome, une lettre d’intention, ou encore une sûreté réelle pour autrui.En second lieu, la proportionnalité permet de lutter contre le gaspillage du crédit des constituants. La perspective est alors différente. Il s’agit d’apprécier l’adéquation entre l’ensemble des sûretés obtenues par un créancier et le montant du crédit garanti. Ce n’est plus la dangerosité excessive de la sûreté pour le garant qui est en cause, mais son inutilité pour le créancier.Bien qu’elles s’inscrivent dans deux fonctions distinctes de la proportionnalité, ces deux règles, qui présentent une communauté de régime, constituent les deux facettes d’un principe général de proportionnalité des sûretés qui émerge en droit contemporain. The thesis proposes to show that the proportionality of security interests fulfils two quite distinct functions.Firstly, proportionality can be required between surety and the warrantor's commitment. It protects the warrantor from insolvency. Proportionality then refers to the adequacy between the amount of the security for third parties and the guarantor's ability to pay. The rule, which is already enshrined in the law on suretyship, deserves to be restricted to guarantors acting in good faith, but also extended to all guarantors who are natural persons, whether they have subscribed to an independent guarantee, a letter of intent or a real security for third parties.Secondly, proportionality can be searched between all the securities offered to the creditor and the loan they are attached to. The perspective is then different. It is a question of assessing the adequacy between the totality of the securities obtained by a creditor and the amount of the secured credit. It is no longer the excessive dangerousness of the security for the guarantor that is at issue, but its uselessness for the creditor.Although some differences between them, those two rules can form, together, a general concept of proportionnality of securities.
Keywords: Abuse; Crédit; Insolvabilité; Principe; Principle; Proportionality; Proportionnalité; Proportionnalité (droit); Securities; Sûretés; Useless; Utilité

دور الضمانات البنكية في مجال التجارة الدولية ( حالة الجزائر) - مشطر, ليلى (جامعة مولود معمري, 2020)
تتضمن التجارة الدولية عددا من المخاطر كسوء تنفيذ أو عدم تنفيذ العقود التجارية الدولية، لذلك من الضروري تأمين جميع الأطراف المتدخلة فيها سواء أكانوا متعاملين تجاريين أو ناقلين أو شركات تأمين أو بنوك،و نظرا للصعوبة التي تثيرها ممارسة حق الرجوع بالنسبة لهذا النوع من المعاملات، فإن الأطراف المعنية تستهدف منذ البداية الحصول على ما تسمى بالضمانات البنكية المستقلة من بينها الضمان بمجرد الطلب، فهو يجسد الخطوة الأولى نحو تبادل تجاري آمن، بحيث يساهم بشكل فعال في تحقيق الضمان الفعلي و الحماية المرجوة بفعل خصائصه الجوهرية المتجسدة أساسا في استقلاله التام عن العقد التجاري الدولي.لقد عرفت الجزائر هذا النوع من الضمانات من الناحية القانونية، غير أن الممارسة العملية له كانت في نطاق محدود جدا، على عكس تقنية الإعتماد المستندي التي تعد من أكثر التقنيات البنكية المستخدمة لتسوية المبادلات التجارية الدولية، يبرز دورها و أهميتها الكبيرة من خلال كفالة مصالح كافة الأطراف من مستوردين و مصدرين و بنوك. Le commerce international comporte un nombre de risques, tels que la mauvaise exécution ou lenon exécution des contrats de commerce international. Par conséquent, il est nécessaire d’accorder une assurance à tous les intervenants à ces contrats, qu’ils soient des opérateurs commerciaux, des transporteurs, des compagnies d’assurances ou banques, et vu la difficulté que soulève l’exercice du droit de retour relativement à ce type de transactions, les parties concernées visent dés le début à obtenir ce que l’on appelle des «garanties bancaires indépendantes ou autonomes», telles que «la garantie bancaire à première demande» qui matérialise le premier pas vers un échange commercial sûr qui contribue efficacement à réaliser la garantie effective et la protection souhaitée à ses caractéristiques essentielles dont principalement son autonomie complète par rapport au contrat commercial international. L’Algérie a connu ce genre de garanties du point de vue législatif, mais sur le plan pratique, l’application demeure très limitée. A l’inverse de la technique du crédit documentaire qui est l’une des techniques bancaires les plus utilisées pour la régularisation des échanges commerciaux internationaux, le rôle et la grande importance de la garantie bancaire à première demande se met en évidence à travers la garantie des intérêts de toutes les parties: importateurs, exportateurs et banques.